Methane production from Sargassum muticum: effects of seasonality and of freshwater washes - Supattra Maneein; John J. Milledge; Patricia J. Harvey; Birthe V. Nielsen (Energy and Built Environment, 2021)
Biogas production from Sargassum muticum, an invasive seaweed species to Europe, is hampered by low methane (CH4) yields during anaerobic digestion (AD), but causes are unclear. This research is the first to demonstrate the impact of extensive freshwater washing of spring- and summer-harvested S. muticum on the CH4 production rates and the biochemical methane potential (BMP). The findings reveal that the rate profile of CH4 production is affected by extensively washing the seaweed and is dependent on seasonality. Spring-harvested S. muticum had higher initial CH4 production rates compared to summer-harvested S. muticum. For spring-harvested S. muticum, the initial rate of CH4 production was lowered by extensive washing. In contrast, extensively washed summer-harvested S. muticum had a higher degradation rate and CH4 production rate relative to its non-extensively washed counterpart. The highest CH4 potentials accumulated by the treated and non-treated S. muticum are, however, statistically similar and not influenced by seasonality or extensive washing (p > 0.05). Potential causes for differences in the rate of CH4 production between summer- and spring-harvested S. muticum are discussed. The differences in CH4 production from treated summer- and spring-harvested S. muticum acts as a stepping stone to understanding the causes for low CH4 yields, which could allow for further enhancements in CH4 production from S. muticum.